Set in Stone? Mobile Practices Evolution in Later Life - Mireia Fernández-Ardèvol; Andrea Rosales; Francisca Morey Cortès (Media and Communication, 2023)
In what ways do mobile communication practices change through later life? To what extent do sociodemographic characteristics, country of residence, and well-being relate to these changing practices? To answer these questions, we used an online, longitudinal study targeting internet users aged 60 and over in six countries (Austria, Canada, Israel, the Netherlands, Spain, and Romania). The focus is on the 3,125 respondents who declared using a mobile phone in every wave (2016, 2018, and 2020). Results show an increasing usage diversification already before the Covid-19 pandemic. A latent class analysis identified three different styles of mobile practices. The most sophisticated relies on almost all the analyzed functions, while the most unsophisticated is limited to voice calls, texting (mainly SMS), and photographs to a lesser extent. Finally, a multinomial analysis provided a picture of the individual characteristics related to the usage styles in the period. The most relevant dimensions were country of residence and age, followed by internet use intensity. The country of residence is relevant to explaining usage because the telecommunications price structure determines the priority given to the mobile phone in (senior) individuals’ everyday lives. The article contributes nuanced evidence of the trajectories of digital practices in later life. At the same time, the findings support and better inform country-based policies, services, and products for more effective inclusion of the older population in today’s hyper-digitized societies.